ESTIMATION OF EARTHQUAKE INSURANCE PREMIUM BY CONSIDERING EARTHQUAKE PROBABILITY AND THE DAMAGE RATIO OF BUILDINGS IN BANDA ACEH AND SIBOLGA CITY - Afifah, Kania Fatin; Lestari, Fuji; Brigitta, Florencia (Journal of Science and Applicative Technology, 2024)
Indonesia is one of the countries prone to earthquakes with significant damage. An area that is frequently hit by earthquakes is Sumatra Island. Several cities, such as Banda Aceh City and Sibolga City on Sumatra Island, quite often experience tremors. For this reason, mitigation efforts are needed through earthquake insurance in managing disaster risk in earthquake-prone areas such as Banda Aceh City and Sibolga City so that it can reduce the impact caused by earthquake disasters. This research aims to determine the probability of an earthquake occurring in Banda Aceh City and Sibolga City using the Probabilistic Seismic Hazard Analysis (PSHA) method. Apart from that, this research also aims to determine the value of the building damage ratio and the estimated value of pure earthquake insurance premiums in Banda Aceh City and Sibolga City. The analysis results show that the estimated pure premium value for residential commercial and industrial building types with less than nine floors in Banda Aceh City is around 2.96 and 21.03 times greater than that of Sibolga City. Meanwhile, the estimated pure premium value for commercial and industrial building types with more than nine floors in Banda Aceh City is more minor, around 6.42 times, compared to Sibolga City.